Time-frequency relationship between innovation and energy demand in Pakistan: evidence from wavelet coherence analysis - Shabbir, Muhammad Salman; Mohd Shariff, Mohd Noor; Asad, Muzaffar; Salman, Rabia; Ahmad, Israr (EconJournals, 2018)
This study examines the empirical relationship of innovation and energy demand by wavelet transform context. This innovative technique allowed the decomposition time-series of different time frequency domains. The continuous wavelet and the wavelet coherence power spectrum is adopted in this study. The relationship between innovation and energy is investigated by using the annual data of Pakistan, from 1997 to 2016 by using three proxies of innovation which includes research & development expenditures, high technology exports, and the number of registered patent by residents. The overall results of the wavelet coherency propose that the measures of innovation are beneficial to bring change in the demand of energy in Pakistan in the long-run period. Furthermore, the results suggested that the technology-oriented innovations have reached to the level of bringing a notable reduction in the level of energy consumption in Pakistan.